Traditional packaging design for local food based on the intangible cultural heritage of Shang-Jin Jun Kiln in Henan Province - BAI Mei (Shipin yu jixie)
Focusing on the Intangible Cultural Heritage project of Shenhou Jun Porcelain in Yuzhou, this study employs methods such as literature review, archaeological findings, and field research to analyze the historical culture, appearance, connotations, and craftsmanship of Shenhou Jun Porcelain. The study summarizes the distinctive features, methods, and patterns of Shenhou Jun Porcelain, and condenses its unique cultural characteristics. It further proposes packaging design strategies that integrate intangible cultural heritage with local food products in Henan, employing techniques such as logo design, graphic design, form design, artistic design, and dynamic design.